PENERAPAN MODEL PEMBELAJARAN SSCS (SEARCH, SOLVE , CREATE, AND SHARE) DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KOMPUTASIONAL SISWA SMP - Ramadhani, Lolita; Handayani, Anik Nur; Srini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the implementation of the SSCS (Search, Solve , Create, Share) learning model in enhancing junior high school students' computational thinking skills. The reSearch employed a mixed methods approach with a descriptive design. The reSearch subjects consisted of 30 seventh-grade students from SMP Negeri 22 Malang and an Informatics subject teacher. The reSearch instruments included teacher observation sheets for managing learning, student activity observation sheets, student response questionnaires, and pretest and posttest assessments to measure improvements in computational thinking abilities.The results showed that the teacher effectively managed the learning process, rated as excellent in the Search and Share phases, and good in the Solve and Create phases. Observations of student activities indicated high levels of engagement, with participation rates reaching 93% in the Search phase and 90% in the Share phase. Students' responses to the SSCS model were very positive, with average questionnaire scores above 4 on almost all indicators. Meanwhile, the pretest and posttest results analyzed using the N-gain method yielded an average score of 0.6394, categorized as moderate improvement. It can be concluded that the implementation of the SSCS learning model is effective in enhancing junior high school students’ computational thinking skills, as indicated by active student engagement, positive responses to the model, and a significant improvement in learning outcomes.